The traditional use of wild edible plants in pastoral and agro-pastoral communities of Mieso District, eastern Ethiopia - Muhidin Tahir; Abdulaziz Abrahim; Tigist Beyene; Gedefa Dinsa; Tilahun Guluma; Yosef Alemneh; Patrick Van Damme; Umer Seid Geletu; Amin Mohammed (Tropical Medicine and Health, 2023)
Abstract Background The populations in Ethiopia have developed their indigenous knowledge to use, manage and conserve wild edible plants (WEPs). In the eastern part of Ethiopia, wild edible plants are used as a means of survival during times of food shortage and as dietary supplements. Documenting the traditional and cultural use of wild food plants is a vital step in obtaining baseline data for investigating nutritional values and possible side effects, preserving indigenous knowledge, and ultimately interesting in wild edible plant conservation. However, their significance, management and utilization have not been documented in Mieso District. Therefore, this study aimed to provide documentation of wild edible plant use associated with ethnobotanical knowledge in Mieso District, eastern Ethiopia. Methods An ethnobotanical study of wild edible plant species was conducted from March 2021 to May 2022. A total of 120 (72 males and 48 females) informants were selected using the snowball method. Data collection methods, including semistructured interviews, direct observation and field walks were used. Data were analysed using descriptive statistics, including independent sample t test and analysis of variance (ANOVA). We calculated use values (UVs) to analyse the relative cultural importance of each plant species. Results A total of 41 wild edible plant species belonging to 33 genera in 21 families were documented to be used as food sources both during times of food shortage and as dietary supplements. Family Malvaceae was best-represented with 6 species, followed by Fabaceae and Rhamnaceae (4 species each). The dominant growth form (habit) was shrubs (30 species), followed by trees (11 species). The most widely used plant parts were fruits (covering 39 species, 95%). The largest number (23 species) was collected from forest habitats only, followed by both village and forest habitats (8 species). The majority of wild edible plants (28 species or 68%) were consumed only during famine or in the time of food shortage ...